2019
DOI: 10.3390/nu11030519
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Demographic and Psychosocial Factors, Barriers to Healthy Eating, and Diet Quality Among African American Adults

Abstract: A healthy diet is associated with lower risk of chronic disease. African Americans generally have poor diet quality and experience a higher burden of many chronic diseases. We examined the associations of demographic and psychosocial factors and barriers to diet quality among African American adults. This cross-sectional study included 100 African American adults in a southeastern metropolitan area. Psychosocial factors (social support, self-efficacy), and barriers to healthy eating were assessed with validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 72 publications
0
13
1
Order By: Relevance
“…HEI total score was not associated with cooking frequency after adjusting for covariates. This may be explained by barriers to healthy eating among Non-Hispanic Blacks, which have been found to potentially decrease total HEI scores [39]. We also did not see an association with cooking frequency and sodium intake or refined grain intake.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…HEI total score was not associated with cooking frequency after adjusting for covariates. This may be explained by barriers to healthy eating among Non-Hispanic Blacks, which have been found to potentially decrease total HEI scores [39]. We also did not see an association with cooking frequency and sodium intake or refined grain intake.…”
Section: Discussioncontrasting
confidence: 70%
“…Two, the loss of a dichotomous relationship by income in our sample may actually represent choices not to cook that differ among SES groups within Non-Hispanic Black adults. For example, although higher income adults may have sufficient choices for food options outside of the home, increased participation in cooking may also be simultaneously influenced by the perception of foods that are culturally congruent or perception of time availability that may dissuade everyday home cooking [38,39]. Our finding suggests the likely importance of available time to cook in our sample in that not working was more likely to be independently associated with high cooking frequency.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As reported previously, black race was an independent risk factor to develop SPMs. Because black men have higher rates of socioeconomic barriers to receive timely, high quality medical care 27 . Interestingly, comparing with other races, the black HNC patients were less prone to suffer from SPMs when they received chemotherapy previously, which needed to be confirmed by further large‐scale clinical observation.…”
Section: Discussionmentioning
confidence: 96%
“…People in the youngest age group (18–29 years) were also more likely than any of the older age groups to intend to adopt personalised nutrition in the future. The positive attitude of younger people is particularly promising, since previous research has indicated that younger people eat less healthy diets than those who are older (Kang et al 2019 ; Roberts et al 2018 ; Martinez-Lacoba et al 2018 ; Ashton et al 2017 ; van Dillen et al 2008 ) and encounter greater barriers in achieving a healthy diet (Adams et al 2019 ). A possible reason that younger people are more favourable toward personalised nutrition, therefore, could be that it is perceived to hold potential to overcome barriers to healthy eating.…”
Section: Discussionmentioning
confidence: 99%